The duration of a co-occurring sound modulates visual detection performance in humans. - Benjamin de Haas (Public Library of Science (PLoS), 2013)
Background The duration of sounds can affect the perceived duration of co-occurring visual stimuli. However, it is unclear whether this is limited to amodal processes of duration perception or affects other non-temporal qualities of visual perception. Methodology/principal findings Here, we tested the hypothesis that visual sensitivity--rather than only the perceived duration of visual stimuli--can be affected by the duration of co-occurring sounds. We found that visual detection sensitivity (d') for unimodal stimuli was higher for stimuli of longer duration. Crucially, in a cross-modal condition, we replicated previous unimodal findings, observing that visual sensitivity was shaped by the duration of co-occurring sounds. When short visual stimuli (∼24 ms) were accompanied by sounds of matching duration, visual sensitivity was decreased relative to the unimodal visual condition. However, when the same visual stimuli were accompanied by longer auditory stimuli (∼60-96 ms), visual sensitivity was increased relative to the performance for ∼24 ms auditory stimuli. Across participants, this sensitivity enhancement was observed within a critical time window of ∼60-96 ms. Moreover, the amplitude of this effect correlated with visual sensitivity enhancement found for longer lasting visual stimuli across participants. Conclusions/significance Our findings show that the duration of co-occurring sounds affects visual perception; it changes visual sensitivity in a similar way as altering the (actual) duration of the visual stimuli does.